THE PERFORMANCE EFFECTS OF SOLID WASTE FROM BAGASSE ON INCREASED OIL RECOVERY - Rini Setiati; S Kasmungin; Sabrina S Riswati; Astri Rinanti; Jochanan Satriabudi (Universitas Trisakti, 2021)
Aims: This study aims to determine the synthesis of bagasse to form surfactants and evaluation of the performance of the sample to increase oil yield. Indonesia generates very large amounts of solid waste, without recycling or adequate management efforts to preserve the environment. Bagasse emerged as one of the most abundant biomass due to the operations of large plantations and factories. Furthermore, previous studies showed extensive uses in the fields of compost, animal feed, bioethanol energy, paper, and reinforced building materials. Methodology and Results: Lignin was extracted from bagasse to process sodium lignosulfonate surfactant (SLS surfactant). The synthesis was characterized several times, and certain examples showed significant HLB values, as a function of emulsion builder. This condition in the oil reservoir is required to reduce interface stress (IFT) and friction in the movement of particles. Another analyses involves the assessment of core flooding of specific synthetic core and crude samples. Conclusion, significance and impact of study: The results confirm the ability of surfactant bagasse to increase oil recovery, namely the HLB value of 11.6. The results also show the surfactant classification with the ability to form a middle-phase emulsion in order to increase petroleum products. Therefore, bagasse as solid waste has a performance effect on the process of increasing petroleum production.